2021
DOI: 10.1017/s0954579420001716
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal cortex and amygdala anatomy in youth with persistent levels of harsh parenting practices and subclinical anxiety symptoms over time during childhood

Abstract: Childhood adversity and anxiety have been associated with increased risk for internalizing disorders later in life and with a range of brain structural abnormalities. However, few studies have examined the link between harsh parenting practices and brain anatomy, outside of severe maltreatment or psychopathology. Moreover, to our knowledge, there has been no research on parenting and subclinical anxiety symptoms which remain persistent over time during childhood (i.e., between 2.5 and 9 years old). Here, we ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…Indeed, of the studies surveyed ( Table 1 ), 47 (57.32%) were cross sectional. Of the papers containing longitudinal data (10 structural MRI and 23 fMRI), only 12 (14.63% of all studies) assessed parenting and brain structure or function and then conducted MRI scans at a later time point ( Whittle et al, 2013a , b , 2016 , 2017 ; Kok et al, 2015 ; Pagliaccio et al, 2015 ; Tyborowska et al, 2018 ; Wang et al, 2019 ; Butterfield et al, 2021 ; Jiang et al, 2021 ; Pozzi et al, 2021 ; Suffren et al, 2021 ), although only five examined brain structural ( Whittle et al, 2013a , b , 2016 , 2017 ) or functional development over time ( Pozzi et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, of the studies surveyed ( Table 1 ), 47 (57.32%) were cross sectional. Of the papers containing longitudinal data (10 structural MRI and 23 fMRI), only 12 (14.63% of all studies) assessed parenting and brain structure or function and then conducted MRI scans at a later time point ( Whittle et al, 2013a , b , 2016 , 2017 ; Kok et al, 2015 ; Pagliaccio et al, 2015 ; Tyborowska et al, 2018 ; Wang et al, 2019 ; Butterfield et al, 2021 ; Jiang et al, 2021 ; Pozzi et al, 2021 ; Suffren et al, 2021 ), although only five examined brain structural ( Whittle et al, 2013a , b , 2016 , 2017 ) or functional development over time ( Pozzi et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have suggested an even earlier deactivation of limbic structures including the hippocampus and the amygdala during stress exposure (Pruessner et al, 2008) In animal models of acute stress (Kassem et al, 2013, Chakraborty et al 2020) and in stress-related mental disorders in humans (Chen et al, 2006;Karl et al, 2006) stress-induced brain structural changes in hippocampus and amygdala are found. At subclinical levels of chronic stress however, some studies did find changes in GMV (Dedovic et al, 2010;Savic, 2015;Suffren et al, 2021;Spalletta et al, 2014), but others did not: GMV reductions associated with stressful life events were, for example, found in the ACC, hippocampus, and parahippocampal gyrus, but not in the amygdala (Papagni et al, 2011) as well as in the MPFC and right insula, but not in the hippocampus or amygdala (Ansell et al, 2012). Possibly, GMV alterations in hippocampus and amygdala may be related to pathophysiological processes in the context of chronic or severe stress (Ansell et al, 2012) rather than the brain response to acute stress.…”
Section: Discussionmentioning
confidence: 99%
“…While reduced hippocampal volume is evident in adults and children exposed to early life stress ( Humphreys et al, 2019 , Marečková et al, 2018 , Woon and Hedges, 2008 ), there is little evidence for an association between hippocampal volume and antenatal stress in humans ( Buss et al, 2012 , Favaro et al, 2015 , Marečková et al, 2018 , Qiu et al, 2013 ). Importantly, few studies have examined the developing brain in very young infants to minimize the impact of the postnatal environment as, for example, parenting styles may also contribute to children’s brain development ( Suffren et al, 2022 ). One recent study reported no association between maternal cortisol concentrations measured in pregnancy and neonatal amygdala volume (age range: 39–46 weeks’ gestation), but found evidence that high cortisol exposure in girls was associated with increased structural connectivity between the amygdala and other brain regions ( Stoye et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%